Dosimetric and Radiobiological Comparison of External Beam Radiotherapy Using Simultaneous Integrated Boost Technique for Esophageal Cancer in Different Location - Wang, Lu; Li, Chengqiang; Meng, Xue; Li, Chengming; Sun, Xindong; Shang, Dongping; Pang, Linlin; Li, Yixiao; Lu, Jie; Yu, Jinming (Frontiers in Oncology, 2019)
Objectives: To compare treatment plans of intensity modulated radiotherapy (IMRT), volumetric modulated arc radiotherapy (VMAT) and helical tomotherapy (HT) with simultaneous integrated boost (SIB) technique for esophageal cancer (EC) of different locations using dosimetry and radiobiology. Methods: 40 EC patients were planned for IMRT, VMAT and HT plans, including 10 cases located in the cervix, upper, middle and lower thorax, respectively. Dose-volume metrics, conformity index (CI), homogeneity index (HI), tumor control probability (TCP) and normal tissue complication probability (NTCP) were analyzed to evaluate treatment plans. Results: HT showed significant improvement over IMRT and VMAT in terms of CI (p=0.007), HI (p<0.001) and TCP (p<0.001) in cervical EC. IMRT yielded more superior CI, HI and TCP compared with VMAT and HT in upper and middle thoracic EC (all p<0.05). Additionally, V30 (27.72±8.67%), mean dose (1801.47±989.58cGy) and NTCP (Niemierko model: 0.44±0.55%; Lyman-Kutcher-Burman model: 0.61±0.59%) of heart in IMRT were sharply reduced than VMAT and HT in middle thoracic EC. For lower thoracic EC, the three techniques offered similar CI and HI (all p>0.05). But VMAT dramatically lowered liver V30 (9.97±2.84%), and reduced NTCP of lungs (Niemierko model: 0.47±0.48%; Lyman-Kutcher-Burman model: 1.41±1.07%) and liver (Niemierko model: 0.10±0.08%; Lyman-Kutcher-Burman model: 0.17±0.17%). Conclusions: HT was a good option for cervical EC with complex target coverage but little lungs and heart involvement as it achieved superior dose conformity and uniformity. Due to potentially improving tumor control and reducing heart dose with acceptable lungs sparing, IMRT was a preferred choice for upper and middle thoracic EC with large lungs involvement. VMAT could ameliorate therapeutic ratio and lower lungs and liver toxicity, which was beneficial for lower thoracic EC with little thoracic involvement but being closer to heart and liver. Individually choosing optimal technique for EC in different location will be warranted.